2020
DOI: 10.3390/brainsci10100692
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Autism: A Field Synopsis and Systematic Meta-Analysis

Abstract: This study aimed to verify noteworthy findings between genetic risk factors and autism spectrum disorder (ASD) by employing the false positive report probability (FPRP) and the Bayesian false-discovery probability (BFDP). PubMed and the Genome-Wide Association Studies (GWAS) catalog were searched from inception to 1 August, 2019. We included meta-analyses on genetic factors of ASD of any study design. Overall, twenty-seven meta-analyses articles from literature searches, and four manually added articles from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…However, these genetic associations did not remain noteworthy after multiple testing correction by BFDP, indicating that these two SNP associations cannot be regarded as robust and conclusive. Similarly, our reanalysis via BFDP of the SNPs discovered in the unique GWAS conducted on patients with CH 41 revealed no noteworthy SNPs at a prior probability of 10 −6 , which is commonly used to test the credibility of SNP associations from GWASs and meta‐analyses of GWASs 50,51 . However, it should be noted that the GWAS of Bacchelli et al 41 included only 99 patients with CH, which is very small in a GWAS setting.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, these genetic associations did not remain noteworthy after multiple testing correction by BFDP, indicating that these two SNP associations cannot be regarded as robust and conclusive. Similarly, our reanalysis via BFDP of the SNPs discovered in the unique GWAS conducted on patients with CH 41 revealed no noteworthy SNPs at a prior probability of 10 −6 , which is commonly used to test the credibility of SNP associations from GWASs and meta‐analyses of GWASs 50,51 . However, it should be noted that the GWAS of Bacchelli et al 41 included only 99 patients with CH, which is very small in a GWAS setting.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, our reanalysis via BFDP of the SNPs discovered in the unique GWAS conducted on patients with CH 41 revealed no noteworthy SNPs at a prior probability of 10 −6 , which is commonly used to test the credibility of SNP associations from GWASs and meta-analyses of GWASs. 50,51 However, it should be noted that the GWAS of Bacchelli et al 41 included only 99 patients with CH, which is very small in a GWAS setting. In addition, the subsequent larger replication study of Ran et al, 43 which enrolled a larger cohort of patients with CH (n = 542), found no association of the two most significant SNPs identified in the GWAS with CH susceptibility, a result that provides further evidence of false-positive results of GWAS findings.…”
Section: Discussionmentioning
confidence: 99%
“…Most often, etiologies of ASD remain unknown. Although, genetic susceptibility has been highlighted as a risk factor 86 . No included studies in our meta-analysis indicated genetic susceptibility.…”
Section: Influence Of Sociodemographic and Other Factorsmentioning
confidence: 99%
“…The study of Panerai and colleagues [18] was aimed to better understand the relationship between sensory and feeding problems in ASD by comparing the sensory responsiveness of ASD children with (ASD-W) and without (ASD-WO) feeding problems. Both groups showed strengths in Visual/Auditory sensitivity, Low-Energy/Weak, and Movement sensitivity, again more marked in ASD-WO.…”
Section: Sensory Profilementioning
confidence: 99%